IDENTIFIKASI TINGGALAN ARKEOLOGI PADA GUA ILETE KECAMATAN BUNGKU TIMUR KABUPATEN MOROWALI - Muktamar Muktamar; Abdul Alim; sandy suseno (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
Based on preliminary observations at Ilete Cave located in Ululere Village, Bungku Timur District, Morowali Regency. In Ilet Cave there are quite a lot of archeological findings such as bones, earthenware fragments, and conch shells. The following environment around the Ilete Cave is composed of the surrounding community plantation land. Based on the issues raised in this study are: (1) What is included in the Ilete Cave of East Bungku District. (2) How is the function of the Cave based on the findings in the Cave Ilete, East Bungku District, Morowali Regency. This study uses the archeological theory of cultural history. This type of research used in this study is qualitative inductive criminal model. Data collection in this research was carried out through literature study, observation or field survey, observation and interview. Analysis of the data applied by the historical method then begins with contextual analysis. The research site shows that the Ilete Cave Site has several artifacts such as pottery fragments, ceramic fragments, bone fragments, teeth and mollusk fragments the authors draw conclusions of the Cave site with the community and reading results.